Image-based multi-scale simulation and experimental validation of thermal conductivity of lanthanum zirconate. (September 2016) - Guo, Xingye; Hu, Bin; Wei, Changdong; Sun, Jiangang; Jung, Yeon-Gil; Li, Li; Knapp, James; Zhang, Jing
Highlights: A novel multi-scale framework to compute thermal conductivity of La2 Zr2 O7 . Single crystal La2 Zr2 O7 thermal conductivity is computed using RNEMD method. Imaged based FE method to calculate La2 Zr2 O7 polycrystalline thermal conductivity. Predicted thermal conductivity is in good agreement with experimental validations. Abstract: Lanthanum zirconate (La2 Zr2 O7 ) is a promising candidate material for thermal barrier coating (TBC) applications due to its low thermal conductivity and high-temperature phase stability. In this work, a novel image-based multi-scale simulation framework combining molecular dynamics (MD) and finite element (FE) calculations is proposed to study the thermal conductivity of La2 Zr2 O7 coatings. Since there is no experimental data of single crystal La2 Zr2 O7 thermal conductivity, a reverse non-equilibrium molecular dynamics (reverse NEMD) approach is first employed to compute the temperature-dependent thermal conductivity of single crystal La2 Zr2 O7 . The single crystal data is then passed to a FE model which takes into account of realistic thermal barrier coating microstructures. The predicted thermal conductivities from the FE model are in good agreement with experimental validations using both flash laser technique and pulsed thermal imaging-multilayer analysis. The framework proposed in this work provides a powerful tool for future design of advanced coating systems.